Processing feasibility study of canning teaching factory (TEFA) fish processing unit in Politeknik Negeri Jember as a medium-large-scale industry - Aulia Brilliantina; Putu Tessa Fadhila; Adi Sucipto; Dimas Triardianto; Suparto Suparto; Yossi Wibisono (AGROINTEK, 2024)
Fisheries are sector with great potential to meet food needs. Teaching Factory Canning Politeknik Negeri Jember (Polije) is one of the Fish Processing Units (UPI) engaged in canning seasoned sardines. Teaching Factory Canning Polije is a UPI included in the medium-large category. This research aims to determine the processing feasibility of canning teaching factory. Data were collected by interview and checklist analysis referring to the Ministry of Marine Affairs, namely the Decree of the Minister of Marine Affairs and Fisheries No.Kep.01/MEN/2007. The application of basic eligibility requirements is carried out by analyzing whether there is a discrepancy with existing regulations or deviations, which are then synchronized with the value of the eligibility criteria. The production process of Teaching Factory Canning has followed the processing feasibility certification set by KKP No.Kep.01/MEN/2007 with good eligibility criteria. The assessment is based on 6 minor deviations, 7 significant deviations, and 1 serious deviation. In addition, the GAP Analysis of the UPI TEFA Canning Polije Processing Feasibility Certification showed that the basic feasibility had met the basic requirements and 1 general requirement by correcting the deviations found